Sensorineural Hearing Loss in Otosclerosis Surgery - Néma, Kristýna; Chrobok, Viktor; Mejzlík, Jan; Pavlík, Vladimír; Školoudík, Lukáš (Acta medica (Hradec Kralove), 2024)
BACKGROUND: During otosclerosis surgery, operative trauma can lead to decreased bone conduction. AIMS: The study aims to observe the bone conduction changes after otosclerosis operations and analyse possible factors affecting the postoperative decrease in bone conduction. MATERIAL AND METHODS: Authors retrospectively processed the data of 109 patients and evaluated pure tone audiometry before surgery and consequently 2 days, 1 month and 1 year after surgery. RESULTS: We noted a deterioration of bone conduction >5 dB on the second postoperative day in 28% (30/109) of patients, which persisted one year after the surgery in 9% (10/109) cases. Analysis of individual factors affecting bone conduction loss revealed a higher risk of permanent loss of bone conduction in patients with early postoperative loss in higher frequencies, in older patients and patients with a preoperative threshold of bone conduction >20 dB. Revision surgery was not a statistically significant factor. CONCLUSION AND SIGNIFICANCE: The bone conduction decrease after otosclerosis surgery is usually temporary. The recovery of bone conduction is influenced by the age of patients and the level of bone conduction before the surgery. The early postoperative decrease of bone conduction in higher frequencies is a negative predictive factor for permanent hearing loss.
Keywords: kostní vedení zvuku; Stapes Surgery; Humans; lidé středního věku; Audiometry, Pure-Tone; Female; Aged; dospělí; audiometrie čistými tóny; Hearing Loss, Sensorineural; senioři; lidé; Adult; Postoperative Complications; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Retrospective Studies; chirurgie třmínku; retrospektivní studie; Bone Conduction; mužské pohlaví; otoskleróza; Otosclerosis; percepční nedoslýchavost